Analisis Penerapan Hukuman Mati dalam Perspektif Hak Asasi Manusia (Studi Kasus Herry Wirawan Putusan Nomor 86/Pid.Sus/2022/PT.BDG) - Anis Nur Fauziyyah MS; Diah Ayu Febrianti; Fella Fahita Ayu Mareza; Filzah Ilda Syafirah; Istiqomah Istiqomah (Jurnal Hukum Lex Generalis, 2022)
The existence of Indonesia as a rule-of-law country has consequences for promoting and protecting human rights which are inherent and cannot be separated because of the presence of the rule of law itself. The application of the death penalty in Indonesia is still a matter of pros and cons in the midst of rampant cases of sexual violence. Based on this polemic, this research focuses on examining whether the death penalty in the case of the decision actually violates human rights or vice versa. The decision stated that the defendant was sentenced to death based on a juridical analysis and the judge's considerations. The application of the death penalty should no longer be enforced in Indonesia because it violates fundamental human rights, namely the right to life.